2017
DOI: 10.1017/s0142716417000029
|View full text |Cite
|
Sign up to set email alerts
|

Morphological awareness: Construct and predictive validity in Arabic

Abstract: The purposes of this study were to examine the dimensions underlying morphological awareness (MA) in Arabic (construct validity) and to determine how well MA predicted reading (predictive validity). Ten MA tasks varying in key dimensions (oral vs. written, single word vs. sentence contexts, and standard vs. local dialect) and two reading tasks (real word and pseudoword reading) were administered to 102 Arabic-speaking Grade 3 children in Abu-Dhabi. Factor analysis of the MA tasks yielded one predominant factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 64 publications
11
46
0
3
Order By: Relevance
“…The results also showed an incremental growth in morphological awareness in both groups as grade-level increased. These results support a strong relationship between morphological awareness and language and literacy development in Arabic (Saiegh-Haddad & Geva, 2008;Tibi & Kirby, 2017).…”
Section: Development Of Morphological Awareness Phonological Awarenesupporting
confidence: 76%
See 2 more Smart Citations
“…The results also showed an incremental growth in morphological awareness in both groups as grade-level increased. These results support a strong relationship between morphological awareness and language and literacy development in Arabic (Saiegh-Haddad & Geva, 2008;Tibi & Kirby, 2017).…”
Section: Development Of Morphological Awareness Phonological Awarenesupporting
confidence: 76%
“…This research has shown this factor to be a reliable predictor of differences between orthographies in reading and spelling development (e.g. Language-specific 2014;Saiegh-Haddad, 2013;Taha & Saiegh-Haddad, 2016;Tibi & Kirby, 2017). Yet, while the developmental trajectories of reading and spelling were shown to be different, the predictors were found to be rather similar with phonemic awareness, the strongest predictor (Caravolas, 2004;Caravolas, Hulme, & Snowling, 2001;Caravolas, Lervåg, Defior, Málková, & Hulme, 2013;Landerl et al, 2012;Ziegler et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Given the morphological richness of Arabic (Saiegh-Haddad and Henkin-Roitfarb, 2014) and the proliferation of morphology in the linguistic and orthographic representation of the word and, in turn, in word reading and spelling in Arabic (Abu-Rabia et al, 2003; Abu-Rabia, 2007; Saiegh-Haddad, 2013, 2017; Taha and Saiegh-Haddad, 2016, 2017; Saiegh-Haddad and Taha, 2017; Tibi and Kirby, 2017), the study of morphological processing in Arabic is highly warranted. Moreover, because there are differences between SpA and StA in inflectional morphology, with some StA inflectional categories not encoded in SpA, such as dual and plural feminine verbal forms, and in derivational morphology, with some StA word-patterns not used in SpA (Saiegh-Haddad and Henkin-Roitfarb, 2014), it is critical to study the role of morphological awareness in reading Arabic, as well as the relevance of SpA morphology in particular to reading in StA (Roman et al, 2009; Wolter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…La conscience morphologique est encore peu étudiée dans une perspective de variables latentes ou de validité de construit (construct validity) (Deacon, Parrila et Kirby, 2008). Bien que certaines études se soient penchées sur les dimensions sous-jacentes à la conscience morphologique en anglais (Muse, 2005;Spencer et al, 2015; et en arabe (Tibi et Kirby 2017), notre étude est à notre connaissance la première à le faire avec un échantillon de francophones. Ainsi, il est légitime de se demander ce que mesurent les différentes tâches de conscience morphologique en français.…”
Section: Synthèse Et Objectifs De Rechercheunclassified